At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

If (x2 +3x +5)(x2 +3x - 5) = m2-n2, then find m ?

Sagot :

[tex](x^2+3x+5)(x^2+3x-5)=m^2-n^2\\\\\ [(x^2+3x)+5][(x^2+3x)-5]=(m+n)(m-n)\\\\m=x^2+3x;\ n=5[/tex]